Performance assessment of infiltration models for varying soil textural classes - Yang, Xiufang; Soomro, Shoukat Ali; Rajani, Vikash Kumar; Li, Bin; Soothar, Rajesh Kumar; Mirjat, Muhammad Uris; Shaikh, Sher Ali; Chandio, Farman Ali (International Journal of Agricultural and Biological Engineering, 2025)
Field experiments were carried out to investigate the soil infiltration rates in different soil textures (clay loam, clay, and silty clay loam) with five infiltration models (Kostiakov, Modified Kostiakov, Philip, Horton, and Green-Ampt). Field experiments were conducted at the experimental stations of Sindh Agriculture University, Tandojam (Station No. 1, Faculty of Agricultural Engineering; 25°25′28′′N, 68°32′24′′E), (Station No. 2, Latif Experimental Farm; 25°26′14′′N, 68°32′30′′E) and Agriculture Research, Tandojam, (Station No. 3, Barley and Wheat Research Institute, 25° 24′ 59′′ N 68° 32′ 40′′ E), Sindh, Pakistan. These stations were selected to meet the need of three different soil textures. The composted soil samples were collected at the depth of 0-30 cm, and their textural classes were determined with the Bouyoucos hydrometer method. Field infiltration rates were measured using a double ring infiltrometer method. The results showed that the initial infiltration rates were high and gradually decreased until they reached a steady state. Using statistical parameters (NSE, RMSE, CC, and R2), the measured infiltration rates were compared with the predicted infiltration rates of the selected infiltration models. For clay loam soil, Philip’s model had the lowest RMSE and highest NSE, CC, and R2 values, followed by Horton’s model. For both clay and silty clay loam soils, Horton’s model was the most accurate in predicting the infiltration rate with lowest RMSE and highest NSE, CC, and R2 values, followed by Philip’s model. The other three models (Kostiakov’s, Modified Kostiakov’s, and Green-Ampt’s) performed poorly with higher errors and lower agreements compared to Horton’s and Philip’s models. In conclusion, Horton’s model demonstrated the highest accuracy and agreement for clay and silty clay loam soils, while Philip’s model showed the best performance for clay loam soil. These findings contribute to understanding the behavior of soil infiltration rate and provide valuable insights for land and water management practices in the studied area. Key words: infiltration models; infiltration rate; texture; predictions DOI: 10.25165/j.ijabe.20251806.9603 Citation: Yang X F, Soomro S A, Rajani V K, Li B, Soothar R K, Mirjat M U, et al. Performance assessment of infiltration models for varying soil textural classes. Int J Agric & Biol Eng, 2025; 18(6): 175–181.